2000
DOI: 10.1046/j.1471-4159.2000.0752546.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization of Neuronal Cells to Oxidative Stress with Mutated Human α‐Synuclein

Abstract: Linkage of ␣-synuclein (␣-SN) mutations to familial Parkinson's disease (PD) and presence of ␣-SN as a major constituent of Lewy body in both sporadic and familial PD implicate ␣-SN abnormality in PD pathogenesis. Here we demonstrate that overexpression of wildtype or mutant ␣-SN does not cause any deleterious effect on the growth or continued propagation of transfected human cells, but overproduction of mutant ␣-SN heightens their sensitivity to menadione-induced oxidative injury. Such enhanced vulnerability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(27 citation statements)
references
References 48 publications
2
25
0
Order By: Relevance
“…This oxidative dimerization was shown to be accelerated in the pathogenic A30P and A53T -synucleins, because of their greater propensity to self-interact [440]. These findings potentially link oxidation and synuclein aggregation to the same pathogenic pathway [440], providing a strong support for the hypothesis that impairments of cellular antioxidative mechanisms and/or overproduction of reactive oxidative species may provoke the initiation and progression of neurodegenerative synucleinopathies [161,163,401,[441][442][443][444].…”
Section: Effects Of Oxidative Modifications: Methionine Oxidationmentioning
confidence: 88%
“…This oxidative dimerization was shown to be accelerated in the pathogenic A30P and A53T -synucleins, because of their greater propensity to self-interact [440]. These findings potentially link oxidation and synuclein aggregation to the same pathogenic pathway [440], providing a strong support for the hypothesis that impairments of cellular antioxidative mechanisms and/or overproduction of reactive oxidative species may provoke the initiation and progression of neurodegenerative synucleinopathies [161,163,401,[441][442][443][444].…”
Section: Effects Of Oxidative Modifications: Methionine Oxidationmentioning
confidence: 88%
“…The generation of ROS by microglia activated by Syn (Thomas et al, 2007) can result in oxidation and nitration of proteins, DNA modifications, and lipid peroxidation, leading to neurotoxicity (Zhang et al, 2005). Oxidation (Ko et al, 2000;Souza et al, 2000) and nitration (Giasson et al, 2000;Souza et al, 2000) of Syn, in turn, can lead to the formation of more aggregates, which could result in increased cytotoxic effects. Consistent with this, Kelly et al have shown that high levels of oxidized cholesterol metabolites in brains from PD and dementia with LB patients, accelerate Syn fibrillation (Bosco et al, 2006).…”
Section: Syn-induced Microglial Activationmentioning
confidence: 99%
“…Other derivatives as Ser/Tyr phosphorylated SN, Tyrnitrosylated SN, Tyr-phosphorylated SN perhaps affect vesicle movement and potentiate fibril formation [157,158]. In addition to SN overexpression in cultured cells, particularly of mutant forms has been linked to mitochondrial deficit [114], defective cellular trafficking [91], impaired chaperone-mediatd autophagy [39] and increased sensitivity to oxidative stress [140].…”
Section: Sn Protein Functionsmentioning
confidence: 99%
“…Three missense mutations have been identified with autosomal dominant inheritance pattern as A53T [140], A30P [140,143], E46K [287]. These missense mutations develop Parkinson's disease at 40-60 years of age with typical PD symptoms.…”
Section: Mutations In Snmentioning
confidence: 99%